2012
DOI: 10.1177/1941406412439414
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Analysis of Standing Desks for Sixth Graders

Abstract: Background. In this pilot study, the authors aimed to examine the implementation of standing desks on classroom performance and behavior. They also examined how the standing desks affected in-class physical activity and body mass index. Methods. Eight sixth graders from Hope Lutheran elementary school participated in the study (age 11.3 ± 0.5 years). Baseline and 8-month postintervention measures were step counts using (W4L Classic pedometers), height, weight, and behavioral markers. Results. Data showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 18 publications
1
68
0
Order By: Relevance
“…Based on Centers for Disease Control and Prevention BMIfor-age percentiles, 28 3 samples had a normal mean BMI (BMI ≥5th and <85th percentiles). 25,26,29 Three other samples were overweight/obese (BMI ≥85th percentile), 27,30,31 and 2 additional studies did not report BMI or height and weight measures to derive BMI. 24,32 Geographically, 4 studies were conducted in the United States, 2 in New Zealand, 1 in Germany, and 1 article reported individual findings from Australia and England.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Centers for Disease Control and Prevention BMIfor-age percentiles, 28 3 samples had a normal mean BMI (BMI ≥5th and <85th percentiles). 25,26,29 Three other samples were overweight/obese (BMI ≥85th percentile), 27,30,31 and 2 additional studies did not report BMI or height and weight measures to derive BMI. 24,32 Geographically, 4 studies were conducted in the United States, 2 in New Zealand, 1 in Germany, and 1 article reported individual findings from Australia and England.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…[30][31][32] The other design was a "sit-to-stand" desk that incorporated both an adjustable standing desk and stool, and some desks included a swinging foot pendulum that permits extra movement and helps to correct posture. [24][25][26][27]29 There were no marked differences in outcomes between standing desk or sit-tostand desk designs; henceforth, the term "standing desk" is used to represent both types of desks. Where applicable, the control condition for each study was a traditional seated desk.…”
Section: Characteristics Of the Relevant Studies Identifi Edmentioning
confidence: 99%
See 1 more Smart Citation
“…interacting with the tablet PC, the motor tasks, and the use of the standing desk, could have focused the child's attention and this could have resulted in more accurate movements when standing This does seem plausible considering that although previous research has reported that while objective measurements showed no difference in 'focus' or attention of participants, all class teachers reported behavioural benefits associated with using standing desks in the classroom (3,24).…”
Section: Discussionmentioning
confidence: 59%
“…There is some evidence that light-intensity levels of PA from dynamic seating are positively related to academic behaviour [10]. Over the past few years, there have been a number of studies conducted to explore the effects of dynamic seating (e.g., standing desks, stability balls, therapy cushions, and cycling desks) versus standard classroom seating on academicrelated outcomes [8,[11][12][13]. One outcome of interest that is associated with student learning and subsequent academic performance is attention.…”
Section: Introductionmentioning
confidence: 99%